The City: Urban Growth Disconnected in the Contexts of Inequality/ Fragmentation/ Segregation in Metropolitan Lima - Ticona Fernandez Davila, Ruben (2021)
This article addresses urban growth in Metropolitan Lima in a context of inequality. It aims to identify the city’s uneven urban growth and the high level of urban fragmentation and segregation that has been predominant over the past decade. It is analyzed from the perspective of urban sociology how a new social, cultural and economic overflow has been produced and reproduced in the city. We maintain that in Metropolitan Lima it has been configured as a segregated and segregated city. Methodologically, a documentary analysis and a review of bibliographic sources are proposed. Finally, by way of conclusions, the need to know and recognize the urban problems of our city is affirmed for a greater efficiency and effectiveness of urban policies.